Identification, molecular evolution, codon bias, and expansion analysis of NLP transcription factor family in foxtail millet (Setaria italica L.) and closely related crops - Chen, Huilong; Liu, Fang; Chen, Jing; Ji, Kexin; Cui, Yutong; Ge, Weina; Wang, Zhenyi (Frontiers in Genetics, 2024)
The NODULE-INCEPTION-like protein (NLP) family is a plant-specific transcription factor (TF) family involved in nitrate transport and assimilation in plants, which are essential for improving plant nitrogen use efficiency. Currently, the molecular nature and evolutionary trajectory of NLP genes in the C4 model crop foxtail millet are unknown. Therefore, we performed a comprehensive analysis of NLP and molecular evolution in foxtail millet by scanning the genomes of foxtail millet and representative species of the plant kingdom. We identified seven NLP genes in the foxtail millet genome, all of which are individually and separately distributed on different chromosomes. They were not structurally identical to each other and were mainly expressed on root tissues. We unearthed two key genes (Si5G004100.1 and Si6G248300.1) with a variety of excellent characteristics. Regarding its molecular evolution, we found that NLP genes in Gramineae mainly underwent dispersed duplication, but maize NLP genes were mainly generated via WGD events. Other factors such as base mutations and natural selection have combined to promote the evolution of NLP genes. Intriguingly, the family in plants showed a gradual expansion during evolution with more duplications than losses, contrary to most gene families. In conclusion, this study advances the use of NLP genetic resources and the understanding of molecular evolution in cereals.